ANALISA INFLASI DAN NILAI TUKAR TERHADAP TINGKAT EKSPOR CRUDE PALM OIL (CPO) - Eva Purnamasari; Ardiansyah Japlani (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2023)
This study aimes to know the influence of inflation and exchange rates on palm oil exports. The data collection method used is a time series from data on export for the period 2018 â€“ 2021, Bank Indonesia, and BAPPENAS. Three hypotheses were built and tested using multiple linear analysis. The data analysis used included autocorrelation test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showes that the inflation variable has a negative effect on crude palm oil exports, and the exchange rate has a negative effect on crude Â palm oil exports. Simultaneously, inflation and the exchange rate have a effect on the export variable of crude palm oil of 67%.